Performance evaluation of four antibiotics using the BD Phoenix™ NMIC-413 antimicrobial susceptibility testing panel for carbapenem-resistant Enterobacteriaceae and carbapenem-resistant Pseudomonas aeruginosa - Guan, Yajuan; Song, Zhenli; Chen, Yanshan; Feng, Jiayu; Fan, Yizhi; Rui, Yongyu (Frontiers in Microbiology, 2025)
BackgroundThe spread of antimicrobial resistance (AMR) poses significant threats to human health. In 2024, the World Health Organization (WHO) classified carbapenem-resistant Enterobacteriaceae (CRE) as a critical-priority pathogen and carbapenem-resistant Pseudomonas aeruginosa (CRPA) as a high-priority pathogen. This study aimed to evaluate the performance of meropenem (MEM), imipenem (IPM), cefepime (FEP), and cefoperazone/sulbactam (SCF) using the BD Phoenix™ NMIC-413 antimicrobial susceptibility testing (AST) panel (NMIC-413 panel) for CRE and CRPA at Nanfang Hospital, China.MethodsA total of 314 archived Gram-negative clinical isolates were tested, including 219 Enterobacteriaceae isolates (150 CRE) and 95 P. aeruginosa isolates (56 CRPA). The NMIC-413 panel and the disk diffusion method were employed for AST of MEM, IPM, FEP, and SCF. Broth microdilution (BMD) was used as the reference method. Categorical agreement (CA), essential agreement (EA), very major errors (VME), major errors (ME), and minor errors (MIE) were calculated. The acceptable standards were as follows: CA and EA > 90%, ME < 3%, and VME < 1.5%.ResultsFor CRE, the NMIC-413 panel met the acceptable standards and demonstrated higher CA values than the disk diffusion method for all four antibiotics (99.3, 96.6, 98.0, and 98.7% vs. 98.7, 96.0, 96.0, and 97.3%, respectively). For CRPA, the NMIC-413 panel also met the acceptable standards and showed superior CA values for MEM and FEP compared to the disk diffusion method (98.2 and 96.4% vs. 96.4 and 92.9%, respectively), while CA values for IPM and SCF were similar between the two methods (98.2 and 92.9% vs. 98.2 and 92.9%, respectively).ConclusionThe NMIC-413 panel demonstrated Clinical Laboratory Standards Institute (CLSI)-compliant performance for all four tested antibiotics against CRE and CRPA, exhibiting superior reliability compared to the conventional disk diffusion method. Future studies should focus on establishing standardized breakpoints for SCF, expanding the detection spectrum for rare bacterial species, and conducting multicenter validation to assess regional variations. We recommend the NMIC-413 panel for AST of CRE and CRPA isolates as a practical alternative to the BMD method.